UNA ESPECIE NUEVA DEL GENERO MIRZAIELLA BASIR, 1942 (NEMATODA: OXYUROIDEA) PARASITO DE DILOBODERUS ABDERUS STURM. (COLEOPTERA: SCARABAEIDAE) DE ARGENTINA - Camino, Nora B. (Instituto de Ecología, A.C., 1969)
Abstract. A new species of the genus Mirzaiella. a parasite of larvae of DHoboderus abderus is described and illustrated. This species is mainly characterized by having in the male, oniy one pair of papillae adanalae; vulva position is nearly 47% of body length, the cloaca is subterminal, and males and females are shorter than the other species of the genus.